The comparison of composite end-points between SGLT-2 inhibitors and placebo in diabetic patients with heart failure with mildly reduced ejection fraction: a meta-analysis of the literature. (3rd October 2022) - Saylik, F; Cinar, T; Selcuk, M; Cicek, V; Hayiroglu, M I; Orhan, A L
Abstract: Background: Sodium–glucose cotransporter 2 (SGLT-2) inhibitors have been found to decrease the incidence and progression of heart failure (HF) with reduced ejection fraction (EF). In the classification of HF, there is a gray zone between HF with reduced EF (EF <40%) and HF with preserved EF (EF >50%), which is named as HF with mildly reduced EF (EF between 40–50%). The effect of SGLT-2 inhibitors in mildly reduced EF HF patients have not yet been well established. We aimed to compare the composite outcomes, including cardiac death and re-hospitalization, between SGLT-2 inhibitors and placebo in this meta-analysis. Methods: We searched MEDLINE, Scopus, EMBASE, Google Scholar, and the Cochrane Library for eligible studies. Of 167 eligible studies, three studies that compared the outcomes between SGLT-2 inhibitors and placebo in mildly reduced EF HF diabetic patients were included in this meta-analysis (n=928) (Table 1). Heterogeneity was assessed using High's I 2, Egger's test and prediction intervals. The pooled effect size was calculated with a fixed-effect model. Due to the total number of studies was lower than 10, we did not report publication bias by drawing Funnel plot. Results: Two studies were randomized controlled trial compared Sotagliflozin and placebo, and one study was an observational study with propensity score matched that compared SGLT-2 inhibitors with placebo. Patients using SGLT-2 inhibitors had lower primary composite end-points, such as cardiac death and re-hospitalization, than patients using placebo (HR= 0.69, 95% confidence intervals = 0.49–0.98, p value = 0.03) (Figure 1). There was no heterogeneity between studies, which was determined with High's I 2 (0%) and Egger's test (p>0.05). Prediction interval was detected as a relatively wide that ranged between 0.30 and 1.58, which concluded that it could be expected to get the results within this range in future studies. Conclusion: This meta-analysis indicated that the composite outcomes, including cardiac death and re-hospitalization, were lower in mildly reduced EF HF diabetic patients using SGLT-2 inhibitors when compared to placebo in such patients. Funding Acknowledgement: Type of funding sources: None.